Personality characteristics in alcohol dependence - Akvardar, Yıldız (Journal of Dependence, 2003)
There is no characteristic personality that can be called the alcoholic personality. However, there are common personality traits and psychodynamic factors that occur in clusters in alcohol dependent patients. Psychoanalysts often noted structural defects, such as ego weakness and diffuculty in maintaining self-esteem as well as defects in self-care. It has been stated that the superego is the part of the mind which is soluble in alcohol. Alcohol use makes the person feel powerful and raise his self-esteem. Typologies of alcoholism has been identified according to the personality characteristics as well. Cloninger identified Type 1 alcoholism as personality characteristics having low novelty seeking, high harm avoidance and high reward dependence, and type 2 alcoholism as personality characteristics of high novelty seeking along with low reward dependence and low harm avoidance. Type 2 alcoholics have having greater rates of aggresiveness, criminality than do Type 1 alcoholics. They were also more extraverted and scored higher on measures of impulsivity and thrill and adventure seeking. Although the biological approach and treatment of all psychiatric disorders have become more prominent nowadays, the personality characteristics are important in the treatment process and prognosis of alcohol dependent patients.
Keywords: Alcohol dependence; personality; self